Mini dental implants retaining mandibular overdentures: A dental practice-based retrospective analysis. Issue 3 (July 2016) - Schwindling, Franz Sebastian; Schwindling, Franz-Peter
Abstract: Purpose: The purpose of this study was to assess the survival of mini dental implants (MDI) and to measure prosthetic maintenance needs in a dental practice-based setting. Methods: Patients with mandibular removable dentures were provided with MDI to improve denture retention. Complications and maintenance were analyzed by use of patient records and evaluated with Kaplan–Meier curves and the log rank test at a significance level of 0.05. Results: Ninety-nine MDI were placed in 25 patients (mean age: 72 years). Two MDI fractured during placement and eight implants failed during the first weeks. No more implants were lost for up to seven years, resulting in 92% survival. Implant survival differed significantly depending on whether the maxilla was provided with complete dentures (94.9%) or with partial dentures (81%). All prostheses were in use at the time of data extraction. Denture base fractures were observed in six cases, an incidence of fractures of 24%. Some minor intervention was necessary: one resin tooth fractured, retention rings were changed in five cases, and repeated relining was required for 16% of the dentures. Conclusions: After mid-term observation, survival of MDI was good. However, the incidence of denture base fractures and of minor prosthetic complications should not be under-estimated.